Path Coefficient-Based Identification of Strategic Selection Targets for Yield and Grain Quality Improvement in Rice - Usharani G; Neeraja C N; Nagesh P; Ramya R; Hemanth K R M; Madhubabu P; Rao D S; Babu V R; Bharathi M; Rani CH V D (The Bioscan, 2013)
Rice (Oryza sativa L.) is one of the most important staple food crops worldwide, and improvement of grain yield along with nutritional quality is a major objective in rice breeding programmes. The present investigation was undertaken to estimate the direct and indirect effects of yield contributing and grain quality traits on grain yield in the rice cross Rpbio-226 × Jalmagna through path coefficient analysis. Six generations namely P₁, P₂, F₁, F₂, BC₁ and BC₂ were developed and evaluated during kharif 2012 under irrigated conditions at the Directorate of Rice Research (DRR), Hyderabad. Observations were recorded for plant height, days to 50% flowering, panicle length, productive tillers per plant, filled grains per panicle, test weight, kernel dimensions, grain iron content, grain zinc content and grain yield per plant. Path coefficient analysis revealed that productive tillers per plant exhibited the highest positive direct effect on grain yield followed by filled grains per panicle, L/B ratio, kernel breadth and plant height, indicating their importance as major selection criteria for yield improvement. In contrast, days to 50% flowering, panicle length, test weight, kernel length, iron content and zinc content showed negative direct effects on yield. The residual effect (0.4134) indicated that the studied traits contributed substantially toward yield variation. The results suggest that emphasis on productive tillers per plant and filled grains per panicle would be effective for identifying superior high yielding segregants with desirable grain quality traits in rice breeding programmes.